A 40-Marker Panel for High Dimensional Characterization of Cancer Immune Microenvironments by Imaging Mass Cytometry - Ijsselsteijn, Marieke E.; van der Breggen, Ruud; Farina Sarasqueta, Arantza; Koning, Frits; de Miranda, Noel F. C. C. (Frontiers in Immunology, 2019)
Abstract Multiplex immunophenotyping technologies are indispensable for a deeper understanding of biological systems. Until recently, high-dimensional cellular analyses implied the loss of tissue context as they were mostly performed in single-cell suspensions. The advent of imaging mass cytometry introduced the possibility to simultaneously detect a multitude of cellular markers in tissue sections. This technique can be applied to various tissue sources including snap-frozen and formalin-fixed, paraffin-embedded (FFPE) tissues. However, a number of methodological challenges must be overcome when developing large antibody panels in order to preserve signal intensity and specificity of antigen detection. We report the development of a 40-marker panel for imaging mass cytometry on FFPE tissues with a particular focus on the study of cancer immune microenvironments. It comprises a variety of immune cell markers including lineage and activation markers as well as surrogates of cancer cell states and tissue-specific markers (e.g. stroma, epithelium, vessels) for cellular contextualization within the tissue. Importantly, we developed an optimized workflow for maximum antibody performance by separating antibodies into two distinct incubation steps, at different temperatures and incubation times, shown to significantly improve immunodetection. Furthermore, we provide insight into the antibody validation process and discuss why some antibodies and/or cellular markers are not compatible with the technique. This work is aimed at supporting the implementation of imaging mass cytometry in other laboratories by describing methodological procedures in detail. Furthermore, the panel described here is an excellent immune monitoring tool that can be readily applied in the context of cancer research.